The Influence of Social Contexts towards the Identity Development of the Main Character in The Bluest Eye By Toni Morrison - Sofiani, Nana; Akhadiah, Sabarti; Emzir, Emzir (Lingua Cultura, 2019)
This research aimed to show how the social contexts influencing the main character of The Bluest Eye, Pecols’s identity development, and the stage of her identity development with the help of Erikson and Marcia’s theories. The research used qualitative research through the literary psychology approach. The data collection had been taken from the novel entitled The Bluest Eye by Toni Morrison, selected and sorted to find out how many among them were supporting the research. The steps were data analysis and data validity. The results show that social contexts greatly affected Pecola’s life, and therefore her identity cannot be developed.; racism, thus, has an influence on all aspects of the black people. Pecola undergoes multiple oppression and abuse as a result of racism, which leads to her self-loathe. She, thus, believes that having blue eyes is the only hope to escape from the suffering she undergoes. It is a warning of identity confusion since she wants to change her identity and becomes white. It pushes her to insanity. Racism and abuse ruin a person’s life by creating hatred and damaged to a person’s soul, and segregate society into groups. It results in the division of groups through the use of terms such as ‘them’ and ‘us’, implying that they are not equal.